Tricksters and cosmopolitans : cross-cultural collaborations in Asian American literary production - Magosaki, Rei (Fordham University Press, 2016)
"Tricksters and Cosmopolitans is the first sustained exploration into the history of cross-cultural collaborations between Asian American writers and their non-Asian American editors and publishers. The volume focuses on the literary production of the cosmopolitan subject, featuring the writers Sui Sin Far, Jessica Hagedorn, Karen Tei Yamashita, Monique Truong, and Min Jin Lee. The newly imagined cosmopolitan subject that emerges from their works dramatically reconfigured Asian American female subjectivity in metropolitan space with a kind of fluidity and ease never before seen. But as Rei Magosaki shows, these narratives also invariably expose the problematic side of this figure, which also serves to perpetuate exploitative structures of Western imperialism and its legacies in late capitalism. Arguing that the actual establishment of such a critical standpoint on imperialism and globalization required the expansive and internationalist vision of editors who supported, cultivated, and promoted these works, Tricksters and Cosmopolitans reveals the negotiations between these authors and their publishers and between the shared investment in both politics and aesthetics that influenced the narrative structure of key works in the Asian American literary canon"-- Provided by publisher
Keywords: American literature -- Asian American authors -- History and criticism.; Authorship -- Collaboration.; Authorship -- Social aspects -- United States.; Authors and publishers -- United States.; Littérature américaine -- Auteurs américains d'origine asiatique -- Histoire et critique.; Coauteurs.; Art d'écrire -- Aspect social -- États-Unis.; Écrivains et éditeurs -- États-Unis.; authors.; LITERARY CRITICISM -- American -- Asian American.; SOCIAL SCIENCE -- Ethnic Studies -- General.; American literature -- Asian American authors; Authors and publishers; Authorship -- Collaboration; Authorship -- Social aspects; United States; Archival Research.; Asian American Editors.; Asian American Literature.; Asian American Writers.; Cosmopolitans.; Globalization.; Jessica Hagedorn.; Karen Tei Yashamita.; Literary Criticism.; Min Jee Lee.; Monique Truong.; Narrative Fiction.; Publishing History.; Sui Sin Far.; Tricksters.; Electronic books.; Criticism, interpretation, etc.